Avaliação de Usabilidade do Aplicativo VLibras-Móvel com Usuários Surdos - Reis , Luana Silva; Araújo , Tiago Maritan U. de; Lima , Maria Dayane F. Cirino; Sales , Angelina S. da Silva; Aguiar, Yuska Paola Costa (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
Accessibility is an important challenge to be faced during the designing of new application, functionalities and technologies. To identify whether the features developed conform to users' characteristics and expectations, usability testing and user experience assessment are common alternatives. These practices are even more necessary when users have some type of disability (sensory, motor, cognitive, intellectual, etc.), because their participation is often neglected in the design process. In this paper, we present a practical case of usability testing and user experience evaluation with the VLibras mobile application, an Assistive Technology for deaf users. This evaluation was carried out with five deaf users, literate in Libras. The results indicate a good acceptance of the mobile version of VLibras, but also indicated the need to make some adjustments in the interface to improve the comprehension of textual elements.